'Racialized Beauty': The Ugly Duckling in Toni Morrison's "God Help the Child" - López Ramírez, Manuela (Complutense Journal of English Studies, 2017)
In God Help the Child, Toni Morrison’s latest novel, set in our contemporary times, her oeuvre seems to have come full circle when she revisits the main themes she dealt with in The Bluest Eye, child abuse and aesthetics relativism. Like her prime novel, her latest narrative is a modern-day fairy tale, a re-interpretation of Hans Christian Andersen’s story “The Ugly Duckling”. Morrison shows how destructive hegemonic female beauty standards and materialistic values are for black females. Lula Ann, like Pecola, their protagonists, illustrate racialized beauty and how African Americans have been colonized by white cultural definitions of beauty, even when the notion “black is beautiful” is commodified. In God Help the Child, Morrison devaluates the myth of racialized beauty and materialism, stressing the need to find your own definitions and self-worth. Like “The Ugly Duckling”, Morrison’s latest novel is a powerful and inspirational metaphor about transformation and self-discovery. At the end of God Help the Child, the signs of hope in The Bluest Eye become an almost fairy-tale ending in Lula Ann’s cathartic journey, her love story and pregnancy.